2019
DOI: 10.1002/jlb.6ru0918-353rrrr
|View full text |Cite
|
Sign up to set email alerts
|

The expanding family of noncanonical regulatory cell subsets

Abstract: The overwhelming body of research on regulatory lymphocytes has focused on CD4+ CD25+ Foxp3+ T cells (regulatory T cells); however, the last 5 years have witnessed inspiring progress in our understanding of regulatory B cells, regulatory CD8+ T cells, regulatory γδ cells, and, more recently, regulatory innate lymphoid cells(ILCregs). This review focuses on these so‐called noncanonical regulatory cell subsets. We primarily survey existing information on the phenotype, function, sustaining factors, and clinical … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
3
0
1

Year Published

2020
2020
2024
2024

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 7 publications
(4 citation statements)
references
References 183 publications
(241 reference statements)
0
3
0
1
Order By: Relevance
“…In the present study, we assessed a core set of immune-regulatory cytokines and found that the key cytokines that discriminate between patients with newly diagnosed ITP and healthy individuals were IL-10, IL-35, and TGF-β 1 , all of which are Tregs-and Bregs-related cytokines. 20 Tregs can be classified into naturally occurring Tregs (nTregs) and induced regulatory T cells (iTr cells). 21 IL-10 is a very important immune regulatory cytokine in preventing inflammatory and autoimmune pathologies and is produced by almost every type of immune cells.…”
Section: Cytokinesmentioning
confidence: 99%
“…In the present study, we assessed a core set of immune-regulatory cytokines and found that the key cytokines that discriminate between patients with newly diagnosed ITP and healthy individuals were IL-10, IL-35, and TGF-β 1 , all of which are Tregs-and Bregs-related cytokines. 20 Tregs can be classified into naturally occurring Tregs (nTregs) and induced regulatory T cells (iTr cells). 21 IL-10 is a very important immune regulatory cytokine in preventing inflammatory and autoimmune pathologies and is produced by almost every type of immune cells.…”
Section: Cytokinesmentioning
confidence: 99%
“…Once activated the immune system clears the pathogenic invasion by various mechanisms described in this chapter. To resolve an immune response different regulatory cell types exist including regulatory CD4 + T cells (Tregs) (18)(19)(20)(21) and regulatory B cells (Bregs) (22,23), regulatory γδ cells (24), regulatory CD8 + T cells (CD8 + Tregs) (25), and regulatory innate lymphoid cells (ILCregs) (26,27). Treg cell-mediated immune regulation is mediated by high IL-2R expression on Treg cells that could deprive effector T cells of IL-2 and thereby inhibit their proliferation (28).…”
Section: Introductionmentioning
confidence: 99%
“…These iTregs play a vital role in maintaining the immune balance by secreting immunosuppressive cytokines, thereby inhibiting atherosclerotic lesion formation [39]. Both natural Tregs and iTregs can prevent autoimmunity and excessive immune responses by suppressing the proliferation and differentiation of naive and effector T cells [40][41][42]. Irrespective of their antigen specificity, Tregs can exert suppressive functions post-activation via antigen presentation.…”
Section: Atherosclerosismentioning
confidence: 99%